The spatial impact of international reconstruction aid in the aftermath of the 2015 Gorkha earthquake: Gentrification and lessons - Karmakar, Ipshita (Nepal Public Policy Review, 2024)
The 2015 Gorkha earthquake in Nepal caused significant property and life loss, triggering a large influx of international reconstruction aid. This paper investigates the spatial implications of this international aid, particularly in Lalitpur. It examines how aid from NGOs and bilateral and multilateral agencies affects urban spaces, including rent, land values, and infrastructure distribution. The study focuses on Wards hosting aid projects and personnel and compares these to earthquake-affected Wards without aid presence as a counterfactual. Two key points emerge: 1) The clustering of aid organization headquarters (operational presence) creates negative externalities, favoring a rentier class over equitable distribution of housing and infrastructure. 2) Aid-funded reconstruction projects (project presence) shift amenities and businesses, accelerating inequity in ways distinct from operational presence. Two Wards in Lalitpur show notable negative impacts, including rising rents, changes in small businesses, and a shift towards catering to the rentier class due to the effects of aid. The research provides policy recommendations for local governments and disaster management authorities in Nepal to address these unequal impacts. Recommendations include monitoring and evaluating aid effects over time, collaboration, and the promotion of transparency in urban development and fiscal resilience.